2013
DOI: 10.1177/0972150913501598
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability Marketing Strategy: An Analysis of Recent Literature

Abstract: The present study reviews the extant literature available on the emerging area of Sustainability Marketing Strategy (SMS), which hopefully, will prove to be a springboard for the future research. Tracing the origin of the concept of SMS, a detailed discussion on historic developments in the field is taken up with the help of definitions and pictorial representation of various related concepts followed by a survey of wide range of available databases from 1996 to 2011. After a rigorous search of numerous journa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0
18

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(69 citation statements)
references
References 89 publications
0
51
0
18
Order By: Relevance
“…While many companies are struggling to form green business strategies, it is not explicitly discussed on the impacts of green marketing strategy on the firms' performance. As suggested by Kumar, Rahman, & Kazmi (2013), very few researches reflecting on sustainability marketing strategy and this area can be explored further. Similarly, Tiwari, Tripathi, Srivastava, & Yadav (2011) claims that the green marketing is still in its infancy and a lot of research is to be done.…”
Section: Sustainabilitymentioning
confidence: 98%
“…While many companies are struggling to form green business strategies, it is not explicitly discussed on the impacts of green marketing strategy on the firms' performance. As suggested by Kumar, Rahman, & Kazmi (2013), very few researches reflecting on sustainability marketing strategy and this area can be explored further. Similarly, Tiwari, Tripathi, Srivastava, & Yadav (2011) claims that the green marketing is still in its infancy and a lot of research is to be done.…”
Section: Sustainabilitymentioning
confidence: 98%
“…Marketing has relevant capability for fostering both sustainable consumption and cleaner production (Dangelico and Vocalelli 2017). Similar to the research on products at farmers markets, marketing strategy applicable to manufactured products often neglects the issue of sustainability (Kumar et al 2013). Good green marketing strategy is based on two concepts for its definition: green marketing and greenwashing (Dangelico and Vocalelli 2017).…”
Section: Ecologically Embedded Productsmentioning
confidence: 99%
“…Conventional MCDM research comprises two major fields: multiple attribute decision-making (MADM) and multiple objective decision-making (MODM), as suggested by previous work (Hwang & Yoon, 1981;Liou & Tzeng, 2012;Zavadskas, Turskis, & Kildienė, 2014;Zeleny, 1982). Both MADM and MODM (or HMCDM) have enticed numerous researchers to employ suitable methods for solving problems in fields like economics (Zavadskas & Turskis, 2011), marketing (Kumar, Rahman, & Kazmi, 2013), e-learning (Zare et al, 2016), finance (Spronk, Steuer, & Zopounidis, 2016;Zopounidis, Galariotis, Doumpos, Sarri, & Andriosopoulos, 2015), construction site selection (Turskis, Zavadskas, Antucheviciene, & Kosareva, 2015), engineering , supplier evaluation and selection (Keshavarz Ghorabaee, Amiri, , supply-chain management (Ansari & Kant, 2017;Soheilirad et al, 2017) and green energy (Kumar et al, 2017). Although those studies have shown various MCDM or HMCDH approaches to decision support, three crucial issues deserve more attention.…”
Section: Introductionmentioning
confidence: 99%